The Implementation of Agile Kanban in the Development of an IoT-Based Sugarcane Growth Monitoring System - Sekar Sari; Oktavia Citra Resmi Rachmawati (Universitas Islam Raden Rahmat, Malang, 2025)
This research stems from the urgent demand for modernisation of sugarcane farming in Indonesia, which faces challenges such as declining productivity due to climate change, limited cultivation technology, and weather uncertainty. The main problem is the absence of a real-time environmental monitoring system that can support farmers in making timely and accurate cultivation decisions. The objective of this study is to develop an IoT-based Sugarcane Growth Monitoring System equipped with four sensors—temperature, humidity, air pressure, and light intensity—using the Agile Kanban project management method. The methodology consists of literature study, planning, implementation, and analysis, carried out iteratively with the aid of a Kanban Board to structure and monitor progress. The results demonstrate that the system successfully integrates hardware, software, and user interfaces to deliver real-time environmental data. At the same time, Agile Kanban proves effective in managing the complexity of the development process. This research contributes not only academically, by showing the applicability of Agile Kanban in agricultural IoT projects, but also practically, by providing sugarcane farmers with decision-making support tools that can enhance efficiency, reduce resource waste, and improve cultivation productivity.